Corporate R&D: A policy target looking for instruments - Pietro Moncada-Paternò-Castello; Keith Smith (European Commission, Joint Research Centre (JRC), 2009)
R&D intensity indicators are increasingly used not only for international comparisons, but also as targets for policies stimulating research. The two are of course intimately linked: it makes little sense to set a quantitative policy target when not knowing whether it is high or low compared to economies at similar stages of development. This paper reflects upon the (Barcelona) target to lift R&D spending to 3% of GDP, set by the EU as a key part of its (Lisbon) strategy for growth and jobs. The paper provides empirical evidence showing the target of 3% of GDP for R&D expenditures in the EU as a whole to be overly ambitious, even though some Member States are above. It also argues that the EU's strategy is short on policy instruments to reach this target. In fact, what appears a simple target actually sums up public R&D, over which decision makers have direct control, and private R&D, which may be partly publicly funded but which can be influenced only indirectly. In this respect, it is clear that national policy-makers have to take into account that the bulk of R&D is conducted by relatively few companies that mostly operate on a global scale.
Keywords: O33; 330; Research and Development; policy targets; international comparison; economic and policy analysis of industrial research